Pengelolaan Projek Penguatan Profil Pelajar Pancasila (P5) Tema Kewirausahaan dan Bangunlah Jiwa Raganya di SMP Negeri 1 Padang - Fauzan, Muhammad; Yahya, Yahya (YASIN, 2025)
Suboptimal management can hinder the achievement of the goals of the Pancasila Student Profile Strengthening Project (P5), thereby limiting the full development of Pancasila student character. This study aims to evaluate the management functions of planning, organizing, actuating, and controlling (POAK) in the implementation of P5 with the themes of Entrepreneurship, Develop the Body and Soul, and Local Wisdom at SMP Negeri 1 Padang. The research method used is descriptive qualitative, with research subjects including the principal, vice principal of curriculum, P5 coordinator, parents, and students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results show that the management of P5 has not yet reached optimal performance. Planning is insufficiently developed, implementation strategies lack structure, monitoring is weak, and reflection is not yet constructive. The conclusion of this study is that the management of P5 at SMP Negeri 1 Padang falls into the category of immature management, where the POAK concepts are understood and designed but their implementation is not yet effective. The implications of this research highlight the need for strengthening the planning, coordination, execution, and evaluation of P5 to ensure that the program is implemented more effectively and produces Pancasila student profiles aligned with the expectations of the Merdeka Curriculum.